Making Italian Jews - Ferrara degli Uberti, Carlotta. author. aut Link
XXIII, 254 p.
Keywords: This book depicts the cultural imagination of the Italian-Jewish minority from the unification of the country to the end of the First World War. The creation of an Italian nation-state introduced new problems and new opportunities for its citizens. What did it mean for the Jewish minority? How could members of the minority combine and redefine Jewishness and Italianness in a radically new political and legal framework? Key concepts such as family, religion, nation, assimilation and – later – Zionism are observed as they shift and change over time. The interaction between the public and private spheres plays a pivotal role in the analysis, and the self-fashioning of Italian Jewish élites is read alongside the evolution of the cultural stereotypes typical of the time. Reinterpreting the Italian national patriotic narrative through the eyes of the Jews, Carlotta Ferrara degli Uberti is able to unveil its less known layers and articulations, while at the same time offering anew perspective from which to read the modern Jewish experience in the Western World. Carlotta Ferrara degli Uberti is Lecturer in Italian History at University College London, UK. She has published extensively on topics of Italian Jewish history.